Simulation of Wearable Microstrip Patch Antenna by Using Textile Material for Ambient RF Energy Harvesting - Batal, Khadija El; Chakhchaoui, Nabil; Eddiai, Adil; Mazroui, M’hammed (International Journal of Membrane Science and Technology, 2023)
Future enhancements in radio frequency (RF) energy harvesting technology will make easy the creation of a network with no need of dedicated transmitters, as a reliable source of wireless energy power. Recently, the development and employment of wearable antennas has increased rapidly for application in the miniaturization of wireless communication devices. The principal feature of wearable antennas is that they are designed as garment elements able to transmit or receive wireless signals. In this context, we propose a design of a wearable textile microstrip patch antenna operating for wireless body area network (WBAN)at the resonance frequency =2.40GHz. The microstrip patch antenna with an edge feeding technique is designed and simulated by using the Keysight Advanced Design System (ADS) software. Textile materials have a low dielectric constant that reduces the surface wave losses and increases the impedance bandwidth of the antenna. The chosen dielectric substrate in this work is the jeans fabric with relative permittivity of 1.70, thickness of 1.00 mm and dissipation factor of 0.025. The antenna performance parameters are obtained from ADS Momentum. Simulation results show that antenna has the gain of 3.22 dBi and directivity of 8.10 dBi, showing that the wearable textile microstrip antenna has a good performance.